Electronic structure of mononuclear and radical-bridged dinuclear cobalt(II) single-molecule magnets - Hunger, David; Netz, Julia; Suhr, Simon; Thirunavukkuarasu, Komalavalli; Engelkamp, Hans; Fåk, Björn; Albold, Uta; Beerhues, Julia; Frey, Wolfgang; Hartenbach, Ingo; Schulze, Michael; Wernsdorfer, Wolfgang; et al. (Nature communications, 2025)
Metal-organic compounds that feature magnetic bistability have been proposed as bits for magnetic storage, but progress has been slow. Four-coordinate cobalt(II) complexes feature high inversion barriers of the magnetic moment, but they lack magnetic bistability. Developing radical-bridged polynuclear systems is a promising strategy to encounter this; however detailed investigations of such species are scarce. We report an air-stable radical-bridged dinuclear cobalt(II) complex, studied by a combination of magnetometry and spectroscopy. Fits of the data give D = −113 cm −1 for the zero-field splitting (ZFS) and J = 390 cm −1 for the metal–radical exchange. Ab initio investigations reveal first-order spin–orbit coupling of the quasi-degenerate d x 2 − y 2 and d x y orbitals to be at the heart of the large ZFS. The corresponding transitions are spectroscopically observed, as are transitions related to the exchange coupling. Finally, signatures of spin-phonon coupling are observed and theoretically analyzed. Furthermore, we demonstrate that the spectral features are not predominantly spin excitations, but largely vibrational in character. Four-coordinate cobalt(II) complexes possess high energy barriers toward inversion of the magnetic moment, but not the magnetic bistability needed for magnetic data storage. Here, the authors report an air-stable radical-bridged binuclear cobalt(II) complex with improved magnetic properties.